Pengaruh Kombinasi Pupuk daun dan Nano silika terhadap Pertumbuhan Anggrek (Dendrobium sp.) pada Subkultur secara In Vitro - Imroatul Khasanah; Erma Prihastanti; Endah Dwi Hastuti; Agus Subagio (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2016)
Orchid is one of the horticulture commodities that are very important in international trade. The problem that is commonly found in the plant tissue culture is hyperhydricity which causes the growth of plant to be too slow. Which is also a problem in acclimatization. Leaf fertilizers contain macro and micro nutrient that promote plant growth. Nano silica is a nutrient which is needed by monocotyl plants to support growth and prevent deficiency or poisoned nutrient. The aim of this research is to know the effects the combination of leaves fertilizer with nano silica and know optimal concentration of leaves fertilizer and nano silica combination to growth of orchids (Dendrobiumsp) in subculture. This research used Completely Randomize Factorial Design (CRFD) (4x2) with four replication. First factor is leaves fertilizer (G) consists of four extent that is G0: 0,000 g/l; G1: 0,250 g/l; G2: 0,375 g/l; G3: 0,500 g/l. Second factor is nano silica (N) that consists of two extent that is N0: 0 ppm; N1: 20 ppm. The parameters which were measured in this research are number of leaves, plant height, number of roots, and the number of shoots. The data were analyzed by Analysis Of Variance (ANOVA) and continued with Duncan’s Multiple Range Test (DMRT) in extent 95%. The results of this research show that there are effects of interaction between leaves fertilizer and nano silica to the amount of roots. Leaves fertilizer does not really affect the orchid but it tends to increase plant height, the amount of shoots and orchid performance. Nano silica does not really affect the orchid but it tends to increase the amount of leaves, plant height and orchid performance. Keyword: Growth, subculture, concentration, leaves fertilizer, nano silica